Effect of Ambarella Leaf Extract on Blood Sugar Levels, Langerhans Islet Diameter, and Hepatosomatic Index of Mice with Diabetes Mellitus Type 2 - Sasmita, Nonik Anggun; Kuswanti, Nur; Khaleyla, Firas (LenteraBio : Berkala Ilmiah Biologi, 2024)
Diabetes mellitus (DM) type 2 caused by obesity and high levels of ROS that trigger hyperglycemia. Ambarella leaf contain flavonoids that has the potential to be used for DM treatment. This study aimed to determine the effect of ambarella leaf extract on blood sugar levels, Langerhans islet diameter, and hepatosomatic index (HSI) of mice with type 2 DM. This study used 6 groups including negative control (KN), positive control (KP), dose 250 mg/kgBW (KA), 350 mg/kgBW (KB), 450 mg/kgBW (KC) and metformin 1,3 mg/20grBW (KM). Blood sugar levels were measured using glucometer, Langerhans islet diameter was measured using imageJ software, and HSI was calculated based on the ratio of hepatic weight to body weight. Data were analyzed statistically using Anova followed by Duncan’s test. The results showed that ambarella leaf extract had an effect on blood sugar level, Langerhans islet diameter, and HSI (p<0.05). The best dose was 450 mg/kg BW (KC) which showed the results of blood sugar levels of 100.75±3.40 mg/dL, Langerhans islet diameter of 101.46±15.42 µm, and HSI value of 4.41±0.31. In conclusion, ambarella leaf extract had an effect on reducing blood sugar levels, improving Langerhans islet diameter, and improving HSI of mice with type 2 DM.